Environmental and Occupational Interventions for Primary Prevention of Cancer: A Cross-Sectorial Policy Framework (2013)
Background: Nearly 13 million new cancer cases and 7.6 million cancer deaths occur worldwide each year; 63% of cancer deaths occur in low- and middle-income countries. A substantial proportion of all cancers are attributable to carcinogenic exposures in the environment and the workplace. Objective: We aimed to develop an evidence-based global vision and strategy for the primary prevention of environmental and occupational cancer. Methods: We identified relevant studies through PubMed by using combinations of the search terms “environmental,” “occupational,” “exposure,” “cancer,” “primary prevention,” and “interventions.” To supplement the literature review, we convened an international conference titled “Environmental and Occupational Determinants of Cancer: Interventions for Primary Prevention” under the auspices of the World Health Organization, in Asturias, Spain, on 17–18 March 2011. Discussion: Many cancers of environmental and occupational origin could be prevented. Prevention is most effectively achieved through primary prevention policies that reduce or eliminate involuntary exposures to proven and probable carcinogens. Such strategies can be implemented in a straightforward and cost-effective way based on current knowledge, and they have the added benefit of synergistically reducing risks for other noncommunicable diseases by reducing exposures to shared risk factors. Conclusions: Opportunities exist to revitalize comprehensive global cancer control policies by incorporating primary interventions against environmental and occupational carcinogens.